Baker, Herbert (Sir) 1902. House for W Wybergh ESQ, Johannesburg. Plans. Watercolour paint and pencil on parchment. - Baker, Herbert (Sir) (My University, 2011)
Baker, Herbert (Sir) 1902 House for W Wybergh ESQ, Johannesburg. Plans. Watercolour paint and pencil on parchment.
Baker, Herbert (Sir) March 1902 House for W Wybergh ESQ, Johannesburg. Plans. Watercolour paint and pencil on parchment. 785x530
Keywords: Baker, herbert (Sir) 1902 House for W Wybergh ESQ, Johannesburg. Plans. Watercolour paint and pencil on parchment.; Baker, Herbert (Sir) 1902 House for W Wybergh ESQ, Johannesburg. Plans. Watercolour paint and pencil on parchment.